The Interpretation and Application of the Most-Favored-Nation Clause in Investment Arbitration - Wang, Anqi (Brill, 2022)
The open access publication of this book has been published with the support of the Swiss National Science Foundation. In The Interpretation and Application of the Most-Favored-Nation Clause in Investment Arbitration, Dr. Anqi Wang provides suggestions for MFN drafting in future international investment agreements (IIAs), as well as for MFN application by investor-state dispute settlement (ISDS) tribunals in case of ambiguity. Dr. Wang conducts a systemic review of MFN clause in history and maps all the relevant ISDS cases. She argues that ISDS tribunals should interpret the MFN clause according to the treaty text on a case-by-case basis, and that tribunals should also consider state consent as the foundation for the jurisdiction of international adjudication, current IIA reform, and essential treaty interpretive principles.